Energy management considering multiple power markets and microgrid storage - Yan, Mengxuan; Li, Zhanlian; Lai, Chun Sing; Zhao, Zhuoli; Zobaa, Ahmed F.; Lai, Loi Lei; Shi, Zebing (Frontiers in Energy Research, 2023)
Storage response highly influences the operational cost of the microgrid. Power market has provided a selection of tariffs which increases difficulties for customer choice. New market entry and traditional tariffs exist together to form a complex market environment. Facing this situation, this paper establishes a complex microgrid market environment with four types of tariffs. By modelling response of electric storage and cold storage in microgrid, a non-linear mixed integer optimization problem is formulated. Numerical studies are implemented for model verification and market performance analysis. Results show that behavior trade-off occurs on different market entries on total cost optimization for microgrid operation.